(untitled) (Vallis Aurea, 2018)
This work reveals the essence of urban agglomeration as one of the forms of territorial organization of settlements. Urban agglomerations are characterized by such properties as the integrity of markets (labor, real estate, land). Creation of agglomeration should meet the conditions of optimal resource supply of life of the population. This requires the establishment of a clear regulatory system based on the program-target approach and the socio-economic concept of agglomeration development.Such a tool is a strategy for socio-economic development. The article also analyzes the prospects of the Odessa agglomeration (Ukraine) in the context of strategic guidelines.